Hyaluronic Acid Facilitates Angiogenesis of Endothelial Colony Forming Cell Combining With Mesenchymal Stem Cell via CD44/ MicroRNA-139-5p Pathway - Luo, Yufang; Liang, Fang; Wan, Xinxing; Liu, Shengping; Fu, Lanfang; Mo, Jiake; Meng, Xubiao; Mo, Zhaohui (Frontiers in Bioengineering and Biotechnology, 2022)
Stem cells and progenitor cells have been identified as potential new therapeutic options for severe limb ischemia to induce angiogenesis, and hyaluronic acid (HA) is commonly applied as a biomaterial in tissue engineering. However, the efficiency of HA combined with human umbilical cord blood-derived endothelial colony forming cells (ECFCs) and human umbilical-derived mesenchymal stem cells (MSCs) on angiogenesis is unclear. In the present study, we showed that HA promoted angiogenesis induced by MSCs-ECFCs in Matrigel plugs and promoted blood perfusion of murine ischemic muscles. Laser confocal microscopy revealed that human-derived cells grew into the host vasculature and formed connections, as shown by mouse-specific CD31+/human-specific CD31+ double staining. In vitro assays revealed that HA supported cell proliferation and migration, enhanced CD44 expression and reduced microRNA (miR)-139-5p expression. Further analysis revealed that miR-139-5p expression was negatively regulated by CD44 in ECFCs. Flow cytometry assays showed that HA increased CD31 positive cells proportion in MSC-ECFC and could be reversed by miR-139-5p mimics transfection. Moreover, the improvement of MSC-ECFC proliferation and migration induced by HA could be blocked by upregulation of miR-139-5p expression. In conclusion, HA facilitates angiogenesis of MSCs-ECFCs, and this positive effect be associated with activation of the CD44/miR-139-5p pathway, providing a promising strategy for improving severe limb ischemia.